3x+7=89-9x

Simple and best practice solution for 3x+7=89-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7=89-9x equation:


Simplifying
3x + 7 = 89 + -9x

Reorder the terms:
7 + 3x = 89 + -9x

Solving
7 + 3x = 89 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
7 + 3x + 9x = 89 + -9x + 9x

Combine like terms: 3x + 9x = 12x
7 + 12x = 89 + -9x + 9x

Combine like terms: -9x + 9x = 0
7 + 12x = 89 + 0
7 + 12x = 89

Add '-7' to each side of the equation.
7 + -7 + 12x = 89 + -7

Combine like terms: 7 + -7 = 0
0 + 12x = 89 + -7
12x = 89 + -7

Combine like terms: 89 + -7 = 82
12x = 82

Divide each side by '12'.
x = 6.833333333

Simplifying
x = 6.833333333

 

You can always share this solution

See similar equations:

| 25=5a-5 | | 8b+5(b-7)=-3+5b | | 6x^2-x=2 | | 32n+12= | | 6(8x-6)=348 | | 127-6x=4x+17 | | 5g-4-6-5g= | | 3+8m=5m+1+4-14 | | 8=-x-3x | | m-5m-9m+3= | | 1+3x=-20+6x | | x^2-18x+82=0 | | 8+2u=-4 | | (3q+7)(4p-5)= | | 18(t-2)+3t=7(3t+4)-10 | | 61=-9-5x | | -19x=-114 | | 4b-4-11b-8= | | 3x+1.1=6x-5.4 | | -66=11n | | 6x+38=13x-18 | | 9x^2+36x=41 | | -9x^2+36x=-41 | | 6y-3+7=y-5y-16 | | -35=-10x-5 | | 21x^3+3x^2+28x+4=0 | | 7+3x=x-5 | | s=120*3.14*r*10 | | 4x+68=10+14 | | 8r+4=84 | | 28x^3+32x^2+35x+40=0 | | 8w=-21+5w | | y^2+19=12y | | 256x^3+500=0 | | y^2+19-12y=0 | | 5x-3=x-11 | | 15x^3+35x^2+6x+14=0 | | 5x-4=54 | | x(2x+3)=-2 | | 28x^3+32x^2+21x+24=0 | | (x-2)(x+2)+18=12 | | x(3x+4)=-2 | | 8z-2=74 | | 15x^3+126x^2-81x=0 | | 7-6(1-x)=2 | | x-(2x-1)=8-(3x+3) | | A=3.14r^2 | | m-7=-12 | | 3ab+6a+5b+10= | | 14m=18+12 | | X^2+3x-26=0 | | 5x^2+18x-35=0 | | 13y=12(y+19) | | y=x^2-18 | | 13y=12 | | y=(3x^4+5x^3-4)-(4x^2-3x+9) | | 4p+7=21 | | (5x^2-3x+22)+(6x^2+6x-67)=y | | (5x^2-3x+22)+(6x^2+6x-67)=0 | | 4.9x^2-5.6x+1.6=0 | | 7x^2+8x-12=0 | | x^2+8x=-4 | | 3w-6=1.5 | | 67=3y+10 | | -7xy+3y-7=0 |

Equations solver categories